2019
DOI: 10.1001/jamadermatol.2019.0315
|View full text |Cite
|
Sign up to set email alerts
|

Association of Psoriasis With Mental Health Disorders in South Korea

Abstract: Nijsten T, Meads DM, de Korte J, et al. Cross-cultural inequivalence of dermatology-specific health-related quality of life instruments in psoriasis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…A study exploring the association of psoriasis with mental health disorders in South Korea found that the risk of depressive episodes, anxiety disorders, somatoform disorders, neurotic disorders and non-organic sleep disorders was 2. 7 However, another study exploring psoriasis and the risk of mental disorders in Denmark found a heightened risk of BP among individuals with psoriasis (HR: 2.33 (95% CI: 1.59 to 3.41). 8 A primary care cohort study from the UK exploring psychiatric morbidities in psoriasis also found higher prevalence for histories of alcohol misuse, BP, depression, anxiety disorder and self-harm in patients with psoriasis.…”
Section: Discussionmentioning
confidence: 98%
“…A study exploring the association of psoriasis with mental health disorders in South Korea found that the risk of depressive episodes, anxiety disorders, somatoform disorders, neurotic disorders and non-organic sleep disorders was 2. 7 However, another study exploring psoriasis and the risk of mental disorders in Denmark found a heightened risk of BP among individuals with psoriasis (HR: 2.33 (95% CI: 1.59 to 3.41). 8 A primary care cohort study from the UK exploring psychiatric morbidities in psoriasis also found higher prevalence for histories of alcohol misuse, BP, depression, anxiety disorder and self-harm in patients with psoriasis.…”
Section: Discussionmentioning
confidence: 98%
“…Our findings are in agreement with those of previous research. 12 However, current study design would more clearly demonstrate the causal relationship between psoriasis and psychiatric diseases as we conducted a prospective cohort study.…”
Section: Discussionmentioning
confidence: 99%
“…22 Another observational study in Korea also showed higher risk of anxiety disorders in patients with psoriasis than in control patients. 12 Psoriasis can be exacerbated by underlying psychiatric diseases like a vicious cycle, when psychiatric diseases worsen the skin disease. There is a biological interconnection between depression, anxiety, and psoriasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence per 10,000 people in Korea increased from 47.4 to 61.5 from 2006 to 2015, with a higher prevalence in men >30 years old [3]. Individuals with psoriasis are at an increased risk of developing other chronic and serious health diseases, including psoriatic arthritis (PsA) (pooled proportion 19.7%; 95% confidence interval [CI] 18.5%-20.9%) [4], type 2 diabetes mellitus (odds ratio [OR] 1.69; 95% CI 1.51-1.89), hypertension (OR 1.43; 95% CI 1.25-1.64) [5], and even depression (OR 2.19; 95% CI 1.97-2.44) [6]. Psoriasis is mainly a dendritic cell-and T-cell-mediated disease, with the production of tumor necrosis factor (TNF)-α and interleukin (IL)-17, 22, 23 [1].…”
Section: Introductionmentioning
confidence: 99%